1987
DOI: 10.2337/diab.36.4.542
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Stimulated Glucose Transport and Insulin Internalization Share a Common Postbinding Step in Adipocytes

Abstract: We recently demonstrated that chymotrypsin substrate analogues inhibit receptor-mediated insulin internalization in isolated rat adipocytes. In this study, the effect on glucose transport of inhibiting insulin internalization with these agents was examined. Glucose transport was assayed by measuring [3H]-2-deoxyglucose uptake, and internalized insulin was measured after rapidly dissociating surface-bound insulin with an acidic buffer. The chymotrypsin substrate analogue N-acetyl-Tyr ethyl ester inhibited insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…A relationship between the biological activity of insulin and the internalization and intracellular processing of the insulinreceptor complex is suggested by various in vitro evidence (14)(15)(16)(17)(18)(19)(20)42). We observed multiple abnormalities of insulin and its receptor internalization and processing in insulinresistant states like obesity and NIDDM.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A relationship between the biological activity of insulin and the internalization and intracellular processing of the insulinreceptor complex is suggested by various in vitro evidence (14)(15)(16)(17)(18)(19)(20)42). We observed multiple abnormalities of insulin and its receptor internalization and processing in insulinresistant states like obesity and NIDDM.…”
Section: Discussionmentioning
confidence: 95%
“…These events involve the recycling and degradation of both insulin and its receptor (10)(11)(12)(13)(14) or their translocation to other intracellular organelles (7)(8)(9).. Past studies suggest that internalization (15)(16)(17)(18) and intracellular processing (19,20) of the insulin-receptor complex may be related to the hormone action.…”
mentioning
confidence: 99%
“…The first step in insulin clearance is binding to its receptor on the cell membrane activating the tyrosine kinase pathway leading to internalization of insulin followed by degradation in lysosomes . In vitro studies have indicated that insulin internalization and insulin action are linked . Thus insulin‐induced insulin receptor activation not only mediates insulin actions but is also involved in its clearance.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with the studies cited above, very rapid actions of insulin, such as stimulation of glucose transport, have been assumed to be exclusively mediated by the initial insulin-receptor interaction at the cell surface Haring et al, 1981) and to be independent of the lysosomal pathway. More recent reports in the literature, however, cast doubt on this assumption, suggesting a possible relationship between insulin processing and stimulation of glucose transport in isolated adipocytes (Frost & Lane, 1985;Jochen & Berhanu, 1987;Hashimoto et al, 1987).…”
Section: Introductionmentioning
confidence: 99%